Pendidikan Inklusif di Era Merdeka Belajar: Pembelajaran dari Diskusi Kelompok Terfokus - Nasir Nasir; Abubakar Abubakar; Rasid Rasid; Titi Fatmawati; Ishak Bagea (Journal of Education and Teaching (JET), 2025)
Inclusive education ensures equal learning opportunities for all students aligning with the goals of the Merdeka Belajar Program. This study explores the implementation of inclusive education in high schools in Kendari City, focusing on challenges and the critical role of school principals, as well as its impact on students with special needs. Using a qualitative approach, data were collected through Focus Group Discussions with school principals, teachers, and stakeholders. Participants were selected based on their involvement in inclusive education, and thematic analysis was conducted to identify key findings. The study highlights three main findings. First, while significant progress has been made in implementing inclusive education, challenges remain, such as limited accessibility and teaching aids. Second, school principals play a key role by formulating strategic policies, supporting teacher development, and fostering collaboration. Third, inclusive education has positively impacted students with special needs, improving their motivation, confidence, and academic performance. However, bullying persists as a major issue requiring joint efforts from schools, parents, and communities. In conclusion, inclusive education under the Merdeka Belajar Program has enhanced learning for students with special needs. To ensure its sustainability, this study recommends strengthening teacher training, improving infrastructure, and promoting community involvement to address remaining challenges.